2018
DOI: 10.1002/suco.201800202
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of target reliability index derivation for reinforced concrete structures governed by serviceability limit state

Abstract: Typical design of reinforced concrete structures is governed by the ultimate limit state (ULS), while serviceability limit state (SLS) is checked. The target reliability index for ULS is recommended based on cost optimization and back calibration of existing practice. Many design cases, such as prestressed concrete, are, however, governed by serviceability conditions and the background for the current recommendations for target reliability index of irreversible SLS as provided by ISO 2394 is unclear. This cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Describe the degradation process of relative dynamic elastic modulus (E s ) using a Wiener process with drift Calculate the drift coefficient μ and the diffusion coefficient Equation (14) shows the relationship between the concrete compressive strength and the degradation amount of relative dynamic elastic modulus. Then, the initial dynamic elastic modulus of C40 concrete is taken as 𝐸 0 = 42.5𝐺𝑝𝑎 and let 𝐸 𝑠 = 𝑥.…”
Section: Calculation Of Statistical Parameters Of Concrete Compressiv...mentioning
confidence: 99%
“…Describe the degradation process of relative dynamic elastic modulus (E s ) using a Wiener process with drift Calculate the drift coefficient μ and the diffusion coefficient Equation (14) shows the relationship between the concrete compressive strength and the degradation amount of relative dynamic elastic modulus. Then, the initial dynamic elastic modulus of C40 concrete is taken as 𝐸 0 = 42.5𝐺𝑝𝑎 and let 𝐸 𝑠 = 𝑥.…”
Section: Calculation Of Statistical Parameters Of Concrete Compressiv...mentioning
confidence: 99%
“…2 to 5, the efficiency of the decision parameter at increasing safety is dependent on the limit state equations for ULS and SLS. Previous research by Van Nierop et al [7][8][9] investigated target reliability in reinforced concrete (RC) structures where the design is governed by SLS considerations. This work indicated that discrepancies exist between the target reliability derived using the generic cost optimization and that derived from a case-specific cost optimization.…”
Section: Efficiency Parametermentioning
confidence: 99%
“…The optimal reliability is found at the decision parameter value that minimizes the structural cost function. Previous research [7][8][9] has shown that in RC structures governed by SLS design, the efficiency of the decision parameter at increasing safety in the limit state equation also plays a role in the determination of the optimum reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Attributed to the different potential failure consequences, the target reliability index of SLS is obvious lower than that of ULS (Lenner et al, 2019;Roubos et al, 2018). According to the suggestion of ISO, the lifetime target reliability index can be taken as 0 and 1.5 when SLS is reversible and irreversible, respectively (ISO2394, 1998).…”
Section: Target Reliability Index Of Slsmentioning
confidence: 99%